Modelo estocástico para dados GNSS e séries temporais de coordenadas GNSS - Marques, Heloísa Alves Silva [UNESP] (2013)
Functional models related to GNSS observations are better known than the stochastic models because the development these last one is more complex. Generally, stochastic models are applied in a simplified form, as the standard model, which assumes that all GNSS measurements have the same variance and are statistically independent, spatially and temporally. However, this assumption does not reflect the reality. Therefore, currently the stochastic models have been investigated more deeply, for instance, considering time correlation, ionospheric scintillation, among others. Brazil is located in the equatorial geomagnetic region and because of this suffers strong influence of ionospheric scintillation and other effects related to the ionosphere. Considering the recent technology of the GNSS receivers, that provide ways to obtain parameters of ionospheric scintillation, this effect is feasible of being considered in the stochastic modeling. Even if an adequate stochastic modeling could be applied in the GNSS data processing, it still may remain non-modeled errors (noise) that can influence the coordinate’s time series, especially those related to factors that go beyond the duration of one day, which is in general the interval (one day) used in the modeling and data processing. Thus, such noise can be characterized from the noise variance components of the time series. Therefore, this research aimed to expand the investigations regarding the stochastic modeling of GNSS observations mainly considering the ionospheric scintillation effects in the Brazilian region. Furthermore, it also aims to perform investigations related to methodologies for the noise characterization in the GNSS coordinates time series and establish a methodology for building functional models of these series...